Vasorelaxation Effect of Estrone Derivate EA204 in Rabbit Aorta. (14th April 2016) - Li, Juan; Li, Wei-Qi; Yao, Yao
Abstract : Estrogen and its derivatives exert vascular protective effects, but the underlying mechanisms remain to be studied fully. Objective . To investigate the vasorelaxation effect and related mechanisms of an estrone derivate EA204[3-(2-piperidin-1-yl)-ethoxy-estra-1, 3, 5 (10)-trien-17-one] on isolated arterial preparation from rabbit thoracic aorta. Methods . Aortic rings from rabbit thoracic aorta were prepared and held in small organ bath filled with Krebs solution; tension change was recorded by a multichannel physiological signal collection and handling system. Results . EA204 (10 −5 to 10 −3  M) induced a concentration-dependent relaxation of aortic rings with endothelium and without endothelium. In denuded arterial preparations, EA204 had a potent relaxing effect on isolated arterial preparations contracted with phenylephrine, norepinephrine, and high-K + solution or BaCl2 . Mechanism study indicates that EA204 relaxes aortic rings by inhibiting Ca 2+ channels (both receptor-operating Ca 2+ channels and the voltage-dependent Ca 2+ channels were involved) to decrease extracellular Ca 2+ influx and intracellular Ca 2+ release. EA204 is different from verapamil, which is a noncompetitive inhibitor of Ca 2+ channels. In addition, K + channels opening may contribute to this vasorelaxation effect. Conclusion . EA204 had a potent endothelium-independent relaxing effect on isolated arterial preparation by inhibiting Ca 2+ channels and opening K + channels. The results suggest that EA204 is a potential compound for treatment of cardiovascular diseases in postmenopausal women.